Seeking God’s will as an obligation of the superiors of religious institutes (Can. 618 CLC /1983) - Szewczul, Bożena (Prawo Kanoniczne, 2023)
One of the obligations of the religious institutes superiors’ is to be docile to the will of God and to govern those subject to them as children of God, as well as the whole communities. Superiors, according to Can. 618 of the Canon Law Code 1983, should be directed to the of the God’s will, and to be first to try to understand it and to docile to it. Authoress tries in Her article to deeply clarify the above mentioned obligation of the superiors, as well as its meaning to the religious life renewal and the spiritual development of the individual religious. For this purpose, in the introduction of the article, She gave a definition of the God’s will and showed Christ as a model for seeking and fulfilling the Father’s will. Then She concentrates herself on a role of the religious superiors’ as mediators conveying the God’s will to their subjects. She also gives the means serving as a help for superiors as well as subjects for recognition of God’s will. This means are: everyday contact with God’s Word, prayer, charisma and Institute own law, instructions of the higher superiors, religious community brotherhood and all life circumstances, that is events and people they met. At the end of the article Authoress describes difficulties the superiors met during their search for God’s will in their religious life.